Three-dimensional morphological study of type B lateral malleolar fractures with special reference to the end-tip location of proximal apexes - Wang, Wei-Bin; Chang, Shi-Min (Frontiers in Bioengineering and Biotechnology, 2023)
Objective To describe the morphological characteristics of Danis-Weber type B lateral malleolar fractures, with special attention on the end-tip locations of fracture apexes, and draw the 3D (three-dimensional) fracture line map. Methods A total of 114 surgically treated cases of type B lateral malleolar fractures were retrospectively reviewed. The baseline data were collected and computed tomography data were reconstructed in 3D model. We measured the morphological characteristics and the end-tip location of the fracture apex on the 3D model. All the fracture lines were superimposed on a template fibula to generate a 3D fracture line map. Results Among these 114 cases, 21 were isolate lateral malleolar fractures, 29 were bimalleolar fractures, and 64 were trimalleolar fractures. All the lateral malleolar fractures in Type B demonstrated a spiral or oblique fracture line. As measured from the distal tibial articular line, the fracture started at -6.22±4.62mm in anterior, terminated at 27.23±12.32mm in posterior, and the average fracture height was 33.45±11.89mm. The fracture line inclination angle was 56.85±9.58˚, and the total fracture spiral angle was 269.81±37.09˚, with fracture spikes of 156.20±24.04˚. The proximal end-tip location of the fracture apex was classified into 4 zones in circumferential cortex: Zone I (lateral ridge) in 7 cases (6.1%), Zone II (posterolateral surface) in 65 cases (57%), Zone III (posterior ridge) in 39 cases (34.2%), and Zone IV (medial surface) in 3 cases (2.6%). Altogether, 43% (49 cases) fracture apexes were not distributed on the posterolateral surface of the fibula, as 34.2% (39 cases) located on the posterior ridge (Zone III). The aforementioned morphological parameters in fractures with Zone-III, sharp spike, and further broken spike, were greater than that in Zone-II, blunt spike, and without further broken spike. 3D fracture map suggested that the fracture lines with Zone-III apex were steeper and longer than that of Zone-II apex. Conclusion Nearly half of type B lateral malleolar fractures had their proximal end-tip of apexes not on the posterolateral surface, which may impair the mechanical application of antiglide plates. A steeper fracture line and longer fracture spike indicate more posteromedial distribution of the fracture end-tip apex.